ANALISIS LAPORAN KEUANGAN RUMAH SAKIT BERDASARKAN KMK NOMOR 1981 TAHUN 2010 PADA RSUD CIMACAN - Afif, Muhammad Nur; Yusuf, Muhammad (JURNAL AKUNIDA, 2017)
This research was intended to determine the application in presentation of financial statements RSUD Cimacan full PPK-BLUD status with reference to the decree of the Minister of health (KMK) number 1981/MENKES/SK/XII/2010 about accounting guidelines of hospital public service agencies approved by Minister of finance number S-5342/MK.5/2010. Data analysis is qualitative descriptive with comparative method that is compare the application and presentation of financial statements prepared by RSUD Cimacan with financial statement based on KMK Number 1981 Year 2010. Complete components of financial statements comprise the balance sheet, operational reports, cash flow statements and notes to financial statements. The results showed that the presentation of financial statements of RSUD Cimacan full BLUD status generally has been in accordance with KMK Number 1981 Year 2010 in representation of financial statements, but have yet to present a cash flow statement based Government Accounting Standarts (SAP) according PP Number 71 Year 2010 for financial reporting entity in terms of consolidation, as well as a need for interested parties.Keywords : PPK-BLUD, KMK Number 1981 Year 2010, Financial statements